2009
DOI: 10.1007/s10530-009-9511-7
|View full text |Cite
|
Sign up to set email alerts
|

Competitive interactions between a native spider (Frontinella communis, Araneae: Linyphiidae) and an invasive spider (Linyphia triangularis, Araneae: Linyphiidae)

Abstract: There are numerous reports of spiders that have become established outside of their native ranges, but few studies examine their impact on native spiders. We examined the effect of the European hammock spider Linyphia triangularis (Araneae, Linyphiidae) on the native bowl-and-doily spider Frontinella communis (Araneae, Linyphiidae) in Acadia National Park, Maine, USA. First, we added L. triangularis to established plots of F. communis. Significantly more F. communis abandoned their webs when L. triangularis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 44 publications
(52 reference statements)
0
18
0
Order By: Relevance
“…As the chances of residents winning agonistic disputes are high and that resident females of L. laeta are particularly aggressive, residentÐintruder agonistic interactions may be at least one of the causal mechanisms underlying the segregated pattern between L. intermedia and L. laeta. Some studies have shown, for instance, that agonistic disputes for web sites and webs per se among spider species of the family Linyphiidae are one of the main mechanisms underlying dynamics of population replacement of native species by exotic ones (Houser 2007, Bednarski et al 2010. Thus, individuals of L. laeta may have been keeping their dominance in the oldest colonization sites, such as old wooden houses, where the species has already established residence before the arrival of L. intermedia, by means of agonistic interactions with intruder spiders that have the same microhabitat preferences, such as the congeneric species L. intermedia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the chances of residents winning agonistic disputes are high and that resident females of L. laeta are particularly aggressive, residentÐintruder agonistic interactions may be at least one of the causal mechanisms underlying the segregated pattern between L. intermedia and L. laeta. Some studies have shown, for instance, that agonistic disputes for web sites and webs per se among spider species of the family Linyphiidae are one of the main mechanisms underlying dynamics of population replacement of native species by exotic ones (Houser 2007, Bednarski et al 2010. Thus, individuals of L. laeta may have been keeping their dominance in the oldest colonization sites, such as old wooden houses, where the species has already established residence before the arrival of L. intermedia, by means of agonistic interactions with intruder spiders that have the same microhabitat preferences, such as the congeneric species L. intermedia.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Scheidler (1989), for example, the density of Theridium impressum L. Koch spiders on thistles is limited by the availability of web sites and regulated by agonistic interactions. However, the results of Bednarski et al (2010) point to agonistic interactions for webs and web sites as a mechanism for dominance and segregation between two species of spider of the family Linyphiidae. Riechert (1982) proposed that territoriality, mediated by agonistic interactions, is a generalized spacing mechanism among spiders.…”
Section: Discussionmentioning
confidence: 99%
“…Related to this is the local displacement of native species by invading species because they share the same niche, which usually concerns closely related species. There are no examples of such a displacement for Europe, but three well-investigated case studies concern theridiids and linyphiids: the North American Steatoda borealis replaced by the European S. bipunctata in anthropogenic habitats in eastern USA and Canada (Nyffeler et al 1986), the endemic New Zealand Latrodectus katipo replaced by the South African Steatoda capensis (Hann 1990), and the North American Frontinella communis locally replaced by the European Linyphia triangularis (Bednarski et al 2010).…”
Section: Impactmentioning
confidence: 99%
“…However, it also has potential for significant ecological impacts. Invasive spider species can harm endemic species through competitive displacement (Nyffeler et al 1986;Hann 1990;Bednarski et al 2010) and invasive arthropod predators can impact on native communities (Snyder and Evans 2006). As a generalist predator, L. hasseltii is likely to eat any appropriately sized insect or arthropod that is caught in its web.…”
Section: Introductionmentioning
confidence: 99%
“…are already found (Levi 1959;Garb et al 2004), and competitive displacement of indigenous Latrodectus spp. by L. hasseltii could occur, as it has in other spiders (Nyffeler et al 1986;Hann 1990;Bednarski et al 2010). Latrodectus geometricus has been accidentally introduced to southern California where it is thought to be displacing L. hesperus (Vincent et al 2009), and in New Zealand there is potential for L. hasseltii to displace L. katipo, a closely related endemic species (Garb et al 2004;Griffiths et al 2005;Vink et al 2008) that is now classified as in ''serious decline'' due to human activities (Patrick 2002;Hitchmough et al 2007).…”
mentioning
confidence: 99%